THE INFLUENCE OF EXCESSIVE LIFTING, AGE, AND WORKING PERIOD ON THE INCIDENCE OF LOW BACK PAIN AMONG TRANSPORT WORKERS - Indarti Trimurtini; Dessy Wijaya; Muhammad Fajar Nurrahman (Fakultas Kedokteran Universitas Jenderal Achmad Yani, 2026)
LBP (Low Back Pain) is the most common musculoskeletal disorder in adults, affecting up to 84% of the population. The Directorate General of Health Services, Ministry of Health of the Republic of Indonesia, reported that approximately 60-80% of individuals worldwide experienced at least one episode of LBP during their lifetime. This study aims to evaluate the influence of excessive lifting, age, and job tenure on the incidence of LBP and its associated disability levels (mild, moderate, and severe) among market porters. The research method used is an observational analytic with a cross-sectional approach. The study sample consisted of 42 male porters who met the inclusion criteria: actively lifting loads greater than 15 kg without equipment, aged 20-60 years, and having a Body Mass Index ≤ 25. Data were collected using the Oswestry Disability Index (ODI) questionnaire and analyzed through the the chi-square and logistic regression tests. The results showed that age had a significant effect on the incidence of LBP (p = 0.000), while job tenure and load weight did not (p > 0.05). Logistic regression analysis revealed that age contributed 61.5% to the incidence of LBP, while job tenure and load weight only contributed 5.9% . In conclusion, although excessive lifting and job tenure positively correlate with the incidence of LBP among porters at the Cimahi Antri Market, these effects are not statistically significant, leaving age is the primary significant determinant. Keywords: low back pain overload, oswestry disability index, porter DOI 10.35990/mk.v9n2.p115-126